2001
DOI: 10.1038/sj.onc.1204128
|View full text |Cite
|
Sign up to set email alerts
|

CD30-mediated cell cycle arrest associated with induced expression of p21CIP1/WAF1 in the anaplastic large cell lymphoma cell line Karpas 299

Abstract: One of the major characteristics of anaplastic large cell lymphomas (ALCL) is the expression of the Ki-1/CD30 antigen. While the receptor mediates NF-kB-activation in Hodgkin's lymphomas, some data suggest the CD30-mediated apoptosis of other CD30-expressing cells. We were able to demonstrate that activation of CD30 leads to dierent eects regarding cell proliferation of the ALCL-derived cell lines Karpas 299 and JB6. Western and Northern blotting analysis revealed that CD30-induced growth inhibition of Karpas … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

6
41
1
1

Year Published

2003
2003
2016
2016

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 60 publications
(49 citation statements)
references
References 39 publications
6
41
1
1
Order By: Relevance
“…(a) p53 expression levels were assessed in four ALK þ ALCL cell lines using western blot analysis and immunohistochemical methods (left panel). Immunoblots showed high levels of p53 in Karpas-299, known to express mt p53 27 and in SUDHL-1, whereas SUP-M2 and DEL expressed low levels (upper left). The Mdm2 protein levels are also shown.…”
Section: Nutlin-3a Inhibits the Growth Of Alk þ Alcl Cells Depending mentioning
confidence: 99%
See 2 more Smart Citations
“…(a) p53 expression levels were assessed in four ALK þ ALCL cell lines using western blot analysis and immunohistochemical methods (left panel). Immunoblots showed high levels of p53 in Karpas-299, known to express mt p53 27 and in SUDHL-1, whereas SUP-M2 and DEL expressed low levels (upper left). The Mdm2 protein levels are also shown.…”
Section: Nutlin-3a Inhibits the Growth Of Alk þ Alcl Cells Depending mentioning
confidence: 99%
“…Direct sequencing of the entire open reading frame of the p53 gene confirmed that SUP-M2 has wt p53, verified the earlier reported nonfunctional p53 mutation at codon 273 in Karpas-299 cells, and identified a different nonfunctional p53 mutation at codon 273 in SUDHL-1 cells. 27,28 DEL cells were found to carry a missense mutation at codon 215 of exon 6, at the DNA binding domain of p53 (Figure 1a). This mutation is reported in the literature as being partially functional, preserving residual p53 transactivation activity for various p53-target genes 29,30 and wt p53 products were not detected at the RNA level in Karpas-299, SUDHL-1, or DEL cells.…”
Section: Expression and Mutation Status Of P53 In Alk þ Alcl Cellsmentioning
confidence: 99%
See 1 more Smart Citation
“…CD30-mediated signal transduction is capable of promoting cell proliferation and cell survival as well as antiproliferative effects and cell death depending on cell type and costimulatory effects (19). Several studies have shown that anti-CD30 monoclonal antibodies possessing signaling properties could inhibit the growth of ALCL cells, but very few of them were effective for HD cells (10,12,13,18). Furthermore, although preclinical studies showed that treatment with anti-CD30 monoclonal antibodies prolonged the survival of ALCLbearing mice significantly, compared with the mice in the control group, many of the mice in the treatment group still died of the disease (15,16).…”
mentioning
confidence: 99%
“…Anti-CD30 monoclonal antibodies have been investigated for the treatment of CD30-expressing malignancies in vitro and in vivo (10,(12)(13)(14)(15)(16)(17)(18). CD30-mediated signal transduction is capable of promoting cell proliferation and cell survival as well as antiproliferative effects and cell death depending on cell type and costimulatory effects (19).…”
mentioning
confidence: 99%